IDENTIFIKASI PENGARUH DUKUNGAN SOSIAL TERHADAP KESEPIAN PADA KARYAWAN RANTAU DI PT. X - Dwi Widarti,; Sitti Rahmah Marsidi, (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2023)
Migrant employees are individuals who work outside their residential areas. Migrant employees not only have to fulfill their tasks and responsibilities as employees but also need to be able to face various challenges as migrants, such as building social relationships in a new environment to gain social support that can suppress feelings of loneliness. This study is a quantitative research aimed at determining the influence of social support on loneliness in migrant employees. The respondents consisted of 81 migrant employees at PT. X who had been working for less than one year. The respondents was selected using purposive sampling technique. Loneliness was measured using a questionnaire based on the theory of Perlman and Peplau, which was modified and adapted from the scale developed by Wanda. Social support was measured using a questionnaire based on the theory of Sarafino and Smith, which was modified and adapted from the scale developed by Ariani. The loneliness scale has a reliability coefficient of 0.887, and the social support scale has a reliability coefficient of 0.876. Based on the data processed using SPSS 25, the coefficient value t = -7.175 and sig (p) = 0.000 (p<0.01), which means that there is a negative influence of social support on loneliness among migrant employees